Peran Psikologi dalam Pendidikan Islam - Darwin; Salami; Mahdhar, Muhammad; Nazarullah, M (Jurnal Ilmiah Guru Madrasah, 2022)
The role of psychology in Islamic education is based on the assumption that there are differences in psychology and the socio-cultural background of students. Psychology is here to bridge the different needs of each student so that educational goals are achieved, namely the transfer of knowledge, ethics, and values to them. The application of psychology in Islamic education is inseparable from the three aspects that make up the human self: the physical, the nafsiah, and the spiritual. These three become essential in applying the psychological approach to Islamic education. On these three fundamental aspects, psychology has three critical roles, namely: (1) The role of psychology in Islamic education as a bio-sociopsychic-spiritual; (2) The role of psychology in Islamic education as a form of one's Islamic character; (3) The role of psychology in Islamic education as a form of spirituality. Abstrak Peran psikologi dalam pendidikan Islam didasari atas asumsi adanya perbedaan psikologi dan latar belakang sosial budaya peserta didik. Sehingga psikologi hadir untuk menjembatani kebutuhan setiap peserta didik yang berbeda agar tujuan pendidikan tercapai, yaitu transfer pengetahuan, etika dan nilai kepada mereka. Penerapan psikologi dalam pendidikan Islam tidak terlepas dari tiga aspek yang membentuk diri manusia, yaitu aspek jasmaniah, aspek nafsiah dan aspek rohaniah. Ketiganya menjadi acuan dasar dalam menerapkan pendekatan psikologi dalam pendidikan Islam. Atas ketiga aspek dasar tersebut, psikologi memiliki tiga peran penting, yaitu: (1) Peran psikologi dalam pendidikan Islam sebagai bio-sosiopsikis-spiritual; (2) Peran psikologi dalam pendidikan Islam sebagai pembentuk karakter Islam seseorang; (3) Peran Psikologi dalam pendidikan Islam sebagai pembentuk spiritualitas.